Electric current activated sintering (ECAS) of undoped and titanium-doped BiFeO3 bulk ceramics with homogeneous microstructure. Issue 6 (June 2019) - Bernardo, Mara S.; Jardiel, Teresa; Caballero, Amador C.; Bram, Martin; Gonzalez-Julian, Jesus; Peiteado, Marco
Abstract: BiFeO3 ceramics have been consolidated applying an electric current activated/assisted sintering (ECAS) methodology under different electrical conditions. DC experiments produce a flash sintering regime by which the bulk cylindrical specimens densify in a few seconds; however, this goes together with a strong localization of the current flow within the material, leading to a dramatic lack of microstructural and compositional homogeneity. The situation changes under the alternate field; a more gradual FAST (Field Assisted Sintering) event is produced which allows the attainment of an exceptional microstructural homogeneity through the whole sintered compacts. Upon Ti-doping the overall diffusivity of the system is delayed but the AC conditions again yield a remarkable microstructural homogeneity in the consolidated material, this time even at the nanoscale level. Accordingly, bulk BiFeO3 ceramics with homogeneous micro-nanostructure can be successfully prepared by an ECAS methodology and at lower temperatures and much shorter times than by conventional solid-state sintering.